Turrana ejuncida, a new species of Acanthocorini (Hemiptera: Heteroptera: Coreidae) from Cape Range, Western Australia, with discussion of its systematic position and host plant associations - Tatarnic, Nikolai J.; Cassis, Gerasimos (Zootaxa, 2022)
The coreid genus Turrana Distant 1911 is redescribed, and a new species Turrana ejuncida sp. nov. is described from specimens collected from Cape Range National Park, Western Australia in 2019 and 2021. Habitus photographs and scanning electron microscopy images are presented of key characters, with X-Ray microtomography deployed to document the male and female genitalia. In addition, DNA barcodes for mitochondrial gene regions COI and 16S were obtained and are made available on Genbank. Finally, the evidence provided in this work is discussed in relation to the systematic position of Turrana.